LEADERSHIP STYLE AMONG MIDDLE MANAGERS IN SAUDI MINISTRY OF HEALTH - AlHarthi, Ayedh Saud; Al Shehri, Othman Ali M.; Al-Khatib, Ahed J. (European Scientific Journal, ESJ, 2013)
﻿﻿﻿Background: Middle managers within ministry of health act under continuous pressure from board level to be successful leaders of today’s and tomorrow’s healthcare service. Leadership styles are important factors among middle managers to retain employees in organizations and to ensure a high quality of practice. Aims: Two main aims: to examine the leadership style(s) of middle managers as perceived by them as leader from different departments of the Saudi Ministry of Health, and to examine the leadership style(s) of the middle managers as perceived by their subordinates as raters from different departments of the Saudi Ministry of Health. Materials and methods: A cross-sectional descriptive design was used to answer the research questions. A convenience sample of 121 participants, 30 middle managers and 91 subordinates, who were recruited through different departments at Saudi Ministry of Health during the period of June 2010 through September 2010.Participants were subjected to Univariate and Multivariate analysis. The Multifactor Leadership Questionnaire (MLQ) was used to collect data. Results: the mean ratings of all four components of transformational leadership for the subordinates and middle managers were between 2.90 to 3.29 .The mean ratings for contingent reward and management by exception active were 3.30 and 2.50 respectively and this was well within the optimum range as suggested by Bass. Management by exception passive and laissez-faire showed mean ratings of 1.67 and 1.25 respectively. The correlation coefficients among transformational leadership style and each variable of, satisfaction, effectiveness and extra effort for raters and leaders sample was high positively reached (r = .72, p< 0.05) , (r = .81, p< 0.05) , (r = .80, p< 0.05) respectively, The correlation coefficients among transactional leadership style and each variable of, satisfaction, effectiveness and extra effort for raters and leaders sample was high positively reached (r = .20, p<﻿﻿﻿0.05) , (r = .44, p< 0.05) , (r = .35, p< 0.05) respectively, and The correlation coefficients among laissez -Faire leadership style and each variable of, satisfaction, effectiveness and extra effort for raters and leaders sample was high negatively reached (r = -.48, p< 0.05) , (r = -.46, p< 0.05) , (r = -.43, p< 0.05) respectively. There are agreement between leaders and raters on transformational, transactional and laissez-faire as distributive in Saudi Ministry of Health in kingdom of Saudi Arabia. The result showed there was no significant difference on the MLQ factors for raters and Leader due to gender, marital status, and age. Also , the analysis showed significant differences among raters’ opinions due to work experiences as contingent reward and extra effort in favor of raters who experience of them more than ˃ 6 Month, and finally, the analysis showed there significant differences among raters’ opinions due to period working with leaders as transformational, idealized Influence attributed, inspirational motivation, intellectual stimulation, contingent reward, and effectiveness in favor of raters who working with leaders for a period between 6 months - ˂ 1 year, but significant differences among raters’ opinions due to period working with leaders as Laissez –Faire in favor of raters who working with leaders for a period between 1 year - 2 years. Conclusions: transformational leadership can contribute a lot to the effectiveness of organizations and that there is a need for further investigation of leadership at different levels.